Decrement Evoked Potential Mapping to Guide Ventricular Tachycardia Ablation: Elucidating the Functional Substrate. Issue 4 (2020) - Bhaskaran, Abhishek; Fitzgerald, John; Nanthakumar, Kumaraswamy; Jackson, Nicholas; Gizurarson, Sigfus; Porta-Sánchez, Andreu
No abstract available